Pengaruh Terapi Oksigen Hiperbarik Terhadap Jumlah Sel Osteosit pada Daerah Tekanan Saat Pergerakan Gigi Ortodonti - Ivan Nicholas Jonathan; Arya Brahmanta; Pambudi Rahardjo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Backgrounds: Orthodontic tooth movement occurs as the result of mechanical force to teeth. Many cells are playing part to correspond the mechanical force, which one of them is osteocyte. Orthodontic force in pressure side induces osteocyte cell death. Hyperbaric oxygen therapy (HBOT) has many benefits, which one of them increases NO, of which can prevents osteocyte apoptosis. Purpose: To determine the influences of 3x30 minutes with 5 minutes break, 2,4 ATA HBOT for 5 and 7 days to osteocyte numbers on pressure side during orthodontic tooth movement. Materials and Methods: This study used “post test only control group” design, 42 guinea pigs were divided into 4 groups. K(-) was a negative control group, K(+) was the orthodontic group, and K1 & K2 were groups that given both orthodontic and HBOT for 5 and 7 days. Osteocyte numbers were counted after HE preparation. Data were analyzed by one way ANOVA and LSD test. Result: Data showed a significant difference of osteocyte amounts between K(-) group and K(+) group and between K(+) with K1 and K2 groups. Conclusions: HBOT for 5 days as well as 7 days gives a significant influences for the increase of osteocyte numbers on pressure side during tooth movement in Cavia cobaya.